Risk management systems in insurance companies - N. V. Kirillova (Мир новой экономики)
The subject of this article is to identify the principal risks of the Russian insurance companies currently, and analysis of risk management systems of Russian insurance companies formed in accordance with the requirements of the insurance market and the legislation in force. There are the formalized risk management framework of Russian insurance companies, is considered a reflection of the elements of risk management systems in the public reporting of insurance companies. Is considered the necessity formalization the risk management of insurers and conditions for this. Article was prepared according to the results of research carried out at the expense of budget funds by the state task Financial University under the Government of Russian Federation.